Comunidades mediadas pela internet: fatores de sucesso e modelo de ciclo de vida - Isoni, Miguel Maurício [UNESP] (2009)
The current study is a descriptive and analytical research which aimed at studying the phenomenon of social network building which takes place in cyberspace, in order to comprehend its fundamentals in IMCs (Internet-Mediated Communities). This way, we wanted to identify the reasons of success and describe the life cycle of such communities. The research general goal was that of identifying the participation and attraction factors for IMC members, throughout their life cycle, whereas its specific goals were: to discriminate IMC defining attributes and success attributes; to discuss association and participation as IMC Success Factors (SF); to describe the SF’s nature for the different perception levels; to identity the SFs which live through the IMC life cycle phases, for each information source (structural, chronological, strategic and environmental); and to discuss SF subgroups according to each IMC’s nature. The research methodology used a “participant observation” type of strategy, at an existing IMC at the Orkut platform, in order to collect and extract agreement levels (high, moderate and low) on thirteen SF (focus, sense of community, technology, service, sociability, members, management, recognition, participation, leadership, reputation, reliability and sustainability), which are fundamental in the IMC’s course for success. The studies that address the holistic notion of IMC life and death are still scarce, thus, this thesis presents the IMC life cycle model (IMC-LCM), picturing the initial steps, of creation, growth, maturity and transformation or death of an existing IMC at the Orkut platform, which counts more than 1200 members to-day. This community was chosen for the adequacy to the adopted methodology. The research used the LimeSurvey software for the database construction, which generated a sample of 104 respondents. This allowed the perceptual mapping... (Complete abstract click electronic access below)